2021
DOI: 10.1002/ejic.202101017
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Catalytic Activity of Mono‐ and Multinuclear Ga Complexes in the ROCOP of Epoxides and Cyclic Anhydrides

Abstract: Tetranuclear Schiff-base complexes L [1][2][3] 2 Ga 4 (t-Bu) 8 1-3 are highly active and selective (> 99 %) catalyst in the alternating ring-opening copolymerization (ROCOP) of epoxides and anhydrides, yielding polyesters with high molecular weights (M n ) and narrow dispersity (Đ). The thermal properties (T g ) of the resulting polyester range from 18 °C to 124 °C and increase with increasing steric bulk or rigidity along the polymer backbone. Comparative studies using structurally related complexes L 4 Ga-(t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 68 publications
2
4
0
Order By: Relevance
“…Interestingly, we found that the reactivity of the DGA monomer was higher than that of GA during ROAC, considering a higher conversion under identical reaction conditions. This higher reactivity of DGA can be mainly attributed to the ring strain and nucleophilicity of anhydride carboxylate as recently demonstrated in the literature. , …”
supporting
confidence: 59%
See 1 more Smart Citation
“…Interestingly, we found that the reactivity of the DGA monomer was higher than that of GA during ROAC, considering a higher conversion under identical reaction conditions. This higher reactivity of DGA can be mainly attributed to the ring strain and nucleophilicity of anhydride carboxylate as recently demonstrated in the literature. , …”
supporting
confidence: 59%
“…This higher reactivity of DGA can be mainly attributed to the ring strain and nucleophilicity of anhydride carboxylate as recently demonstrated in the literature. 27,28 According to previous studies, when the ROAC reaction is catalyzed by the t-BuP 1 /TEB pair and the equivalence of epoxide is typically in excess compared to that of cyclic anhydride, polyether blocks begin to form after all of the cyclic anhydrides are consumed during the synthesis of the polyester. 29 Recently, it was found that the copolymerization of cyclic anhydride and excess epoxide at elevated temperatures was free of polyether formation when catalyzed by the t-BuP 1 /TEB pair, even after complete anhydride consumption.…”
mentioning
confidence: 99%
“…This phenomenon has been previously reported in polyesters synthesized via the ROCOP of cyclic anhydrides (DGA and GA) and epoxides. 34 The hyperbranched polyester P(TA-alt-EPO) exhibited a higher T g of 60.8 °C. These findings indicate that the polyesters synthesized using bicyclic anhydrides (PA) and tricyclic anhydrides (NA) generally show much higher T g values than those synthesized using monocyclic anhydrides (DGA and GA).…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…These T g values are significantly lower than the T g values of alternate poly(PA- alt -CPO) and poly(PA- alt -PO) reported at 48 and 40 °C, respectively. 53…”
Section: Resultsmentioning
confidence: 99%
“…These T g values are significantly lower than the T g values of alternate poly(PA-alt-CPO) and poly(PA-alt-PO) reported at 48 and 40 °C, respectively. 53 Synthesis of poly(AB x -b-PLA) and AB x -based polyurethane Because SnOct 2 is a common catalyst for ROP of cyclic esters, such as lactides, it is therefore possible that SnOct 2 can be used to combine AB x polymers in one pot with biodegradable polylactides widely used in food packaging and biomedical applications. MA was selected as a model cyclic anhydride because it contains a double bond capable of post-polymerization modifications if needed.…”
Section: Papermentioning
confidence: 99%